To examine satisfaction with body image and body mass index in schoolchildren, taking into account the differences between the sexes (Research, Society and Development, 2025)
This study aimed to evaluate the association between body dissatisfaction and body mass index (BMI) in elementary school students. The sample consisted of 38 schoolchildren, with a mean age of 8.44 years (±1.10), of which 57.9% were male and 42.1% were female. Body dissatisfaction was assessed using the Software for Body Perception Assessment (S.A.P.E.C.O), and nutritional status was determined by BMI. The results revealed a high prevalence of body dissatisfaction (84.2%), with significant differences between sexes: girls showed greater dissatisfaction related to excess weight (41.2%), while boys demonstrated greater dissatisfaction with thinness (73.3%). No statistically significant association was found between BMI and body dissatisfaction (p > 0.05). It is concluded that body dissatisfaction is a prevalent phenomenon among schoolchildren, with differences associated with sex, highlighting the need for educational and psychological interventions to promote a positive self-image and prevent eating and emotional disorders.